Impact of varying Li2CO3 additions on the hydration of ternary CSA-OPC-anhydrite mixes. (May 2020) - Wolf, J.J.; Jansen, D.; Goetz-Neunhoeffer, F.; Neubauer, J.
Abstract: The effects of varying Li2 CO3 additions on the hydration kinetics of a ternary CSA-OPC-anhydrite system were investigated. The presence of Li led to increased ye'elimite and C3 S dissolution as well as accelerated ettringite precipitation. Excessive additions however resulted in heavily decreased ye'elimite dissolution and hydration kinetics after the initial period as evidenced by heat-flow-calorimetry and in-situ XRD. Pore solution analysis showed that the decreased ye'elimite dissolution can be linked to remarkably high Ca/Al-ratios which correspond to the induction period in CSA based systems combined with retarding agents. The early precipitated silicon incorporating hydrate phase in these systems is either straetlingite or a zeolitic phase. The high Li-addition led to a dissolution of these phases in favor of C-S-H precipitation. Consequently, the formed hydrate phase assemblage was changed from ettringite, AH3 and straetlingite or Ca-zeolite in the reference and low Li2 CO3 system to ettringite and C-S-H precipitation in the highly dosed Li system.